2020
DOI: 10.1016/j.eats.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Remnant-Preserving Double-Bundle ACL Reconstruction With a New Remnant Augmentation Technique

Abstract: Anterior cruciate ligament (ACL) remnant preservation techniques have been recently introduced for covering the graft with remnant to improve the clinical results of ACL reconstruction. Several theoretical advantages exist for this technique; however, clinical results remain inconsistent and controversial. We have focused on the biomechanical function of the remnant and have been performing a new remnant-preserving reconstruction procedure that augments the graft with residual remnant. Preserving the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In comparing the three groups in this study, the group that underwent new remnant-preserving anatomical double-bundle ACL reconstruction 16 showed no significant differences in clinical scores compared to the resected remnant group and the absent group. However, the preserved group had significantly better anterior stability than both the resected and absent groups.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In comparing the three groups in this study, the group that underwent new remnant-preserving anatomical double-bundle ACL reconstruction 16 showed no significant differences in clinical scores compared to the resected remnant group and the absent group. However, the preserved group had significantly better anterior stability than both the resected and absent groups.…”
Section: Discussionmentioning
confidence: 66%
“…Surgery was performed based on the method described by Tensho et al. 16 The patient was placed in the supine position, and the affected limb was flexed 90° at the knee joint. In preparing the graft tendon, the ipsilateral semitendinosus tendon and, in some cases, the gracilis tendon were double- or quadruple-bundled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept has led to increased interest in studies of remnant preservation, proven by the recent surge in publications in the field of repair and remnant preservation. 2 , 3 , 6 , 7 , 8 , 12 Because of newer information about the remnant, ACL is now considered as an organ with neural and vascular tissues and not merely a stabilizing structure. 11 Many histologic studies have confirmed that remnants of torn ACL retain vascularized synovial sheets, numerous fibroblasts and myofibroblasts, and various mechanoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…5 Various techniques of remnant tensioning are described in the literature, but they are technically demanding and difficult to replicate. [6][7][8] Some of these techniques need separate fixation devices for the remnant, making those techniques costly and nonanatomical. 6 Some require a sizeable outside incision to secure remnant sutures, whereas some require tampering with a primary suspensory fixation device for graft.…”
mentioning
confidence: 99%